“‘This horrible patrimony’: Masculinity, War and the Upper Classes in Jessie Douglas Kerruish’s The Undying Monster.” - Mercer E (Edinburgh University Press for the International Gothic Association, 2020)
The recent reissue of Jessie Douglas Kerruish’s critically neglected Gothic novel The Undying Monster: A Tale of the Fifth Dimension (1922) describes it as ‘dated’ but its more conservative elements nevertheless exist alongside a subversive thrust. Published just four years after the end of the First World War, the novel extols the nobility of the landed gentry, positioning protagonist Oliver Hammand as representative of a positive tradition that guarantees social order in a time of chaos, while simultaneously discrediting the upper class by depicting Oliver as an untamed beast that threatens social order. The Undying Monster has something to add to understandings of Gothic narratives that use the figure of the werewolf to explore the sinister side of masculinity, in particular the possibility that depravity might belong to the upper classes, rather than the lower class as was popularly imagined.
Keywords: Class; First World War; Masculinity; Werewolf literature; 2005 Literary Studies